Strategi Digital Marketing Pada UMKM Roti Satria Oen Akbar Bakery Untuk Mempertahankan Daya Saing - Rakhmawati Purba; Bunga Sabrina; Meika Andini; Miftahul Jannah; Nadya Indayani; Rumiris Siahaan; Abednego Abednego; Rizki Wulanita Batubara; Viktor Viktor (STIE Bina Karya, 2026)
MSMEs play a vital role in the Indonesian economy, creating jobs, increasing income, and driving regional economic growth. One MSME operating in the culinary sector is Roti Satria Oen Akbar Bakery. It is a bakery offering a variety of bread and cake products. Competition in the bakery business is currently intensifying, marked by the emergence of many similar businesses offering products with a variety of flavors, prices, and quality, as well as attractive promotions through digital media. Digital marketing is a marketing medium currently in high demand by the public to support various activities. One of the economic strengths that has been supporting the Indonesian economy and regional economies is the presence of micro, small, and medium enterprises (MSMEs). To maintain its competitiveness, Roti Satria Oen Akbar Bakery continues to improve its marketing aspects, including more attractive packaging designs and improving business legality, in addition to maintaining product quality. Roti Satria Oen Akbar Bakery needs to maximize social media by creating engaging content, utilizing paid advertising, and collaborating with influencers to increase market reach.